Korelasi antara Kompetensi Kepribadian Guru dengan Minat dan Aktifitas Belajar Siswa di Madrasah Aliyah Samarinda - Rahmiyati, Yunik (SYAMIL, 2016)
This research based on the phenomena on the field which are the correlation between the competence of teachers personality and interests of student in learning activities on islamic education learning at Madrasah Aliyah (MA) in Samarinda. The aim of the research is to descript the competence of the teacherâs personality, interest of student in learning activities. Therefore, to identify how much the correlation between the competence of the teachers personality and interests of student in learning activities partially is and to identify how much the correlation between the competence of the teachers personality and interests of student in learning activities on Islamic education learning at Madrasah Aliyah (MA) in Samarinda. The result showed that sBoth competence of teacherâs personality and students learning activity had a very strong correlation about r=0.989 which mean the competence of teacherâs personality, studentâs interest and learning activity had an average correlation about 97.8% and the rest of 2.2% was defined in other variables. The hypothesis showed that there was a significance correlation between competence of teacherâs personality and the learning activity were accepted as true by value (Fcount = 4246.876 ; sig. = 0,000).